(untitled) (The Sudan Journal Of Animal Production المجلة السودانية للانتاج الحيواني, 2021)
Growth performance and feed utilizationby Sudan Desert lambs fed onconcentrate and roughage ration supplemented with Moringa (Moringa oleifera) shoots Nuha H. Talib1, Afaf A. Mabrouk1, Hala E. Elawad1, and Y. R. Sulieman2 1Animal Production Research Centre, Khartoum north, Hillat Kuku-Sudan 2 University of Bahri, College of Animal Production, Alkadaru-Kartoum North- Sudan This work was supported by Animal Production Research Centre (APRC). Correspondence to first author Nuha. H. Talib (e-mail: nuhahamed0123@hotmail.com). Summary An experiment was carried out to evaluate the growth performance and feed utilization by Sudan Desert lambs fed concentrate diet (25% sorghum grains, 40% wheat bran, 32% groundnut cake, 2% lime stone and 1% common salt on fed basis) and roughages supplemented with graded levels of Moringa oleifera shoots. Eighteen intact Sudan Desert lambs were allocated to two levels of sun-dried Moringa oleifera shoots (200 and 400 g/animal/day) and control diet (0 inclusion of Moringa oleifera). All of the experimental lambs received a basal concentrate diet of 150 g/animal/day and alfalfa forage ad libitum. The design was a complete randomized design (CRD) with 6 animals per treatment. Lambs were fed in groups. The daily weight gain (146.8- 163.6 g) of the lambs under study were the same (P>0.05) when fed on different treatments. The feeding period of sheep targeted for 40 kg live weight was not significantly (p>0.05) different between treatment groups. Furthermore, digestibility of dry matter, organic matter, crude protein (g/kg) of different treatments was not influenced by using moringa shoots as roughage source. It was concluded that supplementation with Moringa oleifera shoots up to 400g/animal/day has no negative effect on either lamb performance or feed utilization suggesting higher inclusion rates. Keywords: feed utilization, lambs, moringa.